The Gruffalo Little Library. 2, Colours - Donaldson, Julia; Scheffler, Axel, 1957- (London : Macmillan children's books, 2011)
Learn colours with Gruffalo.
On the cover: Perfect for small paws!
Based on the picture book by Julia Donaldson and Axel Scheffler.
Keywords: farby; Colours; leporelá; cudzojazyčná literatúra; čítame si spolu 0+